STRATEGI DAN TANTANGAN PRESERVASI DIGITAL DI PERPUSTAKAAN - Cyntyawati, Ni Ketut Nila; Ginting, Richard Togaranta; Suhartika, I Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 3 No 1 (2023), 2023)
This research purposes the strategies and challenges of digital preservation in libraries. This research uses a literature study because the data is collected through books, journal, and other sources. Data analysis which consists of data reduction, data presentation and drawing conclusions. The data collection technique in this research is by reading several source, analyzing the data, and concluding data. The result of this research found that there are several digital preservation strategies in the library such as technology preservation, refresh or update, migration, emulation, digital archeology, and converting digital data to analog. Libraries in carrying out digital preservation activities certainly have challenges that must be faced, such as the relatively short age of storage media, obsolescence of equipment, information security, and sudden loss of digital collection. Keywords: digital library, digital collection, digital preservation strategy, digital preservation challenges.